The effect of time-dependent macromolecular crowding on the kinetics of protein aggregation: a simple model for the onset of age-related neurodegenerative disease - Minton, Allen P. (Frontiers in Physics, 2014)
A linear increase in the concentration of “inert” macromolecules with time is incorporated into simple excluded volume models for protein condensation or fibrillation. Such models predict a long latent period during which no significant amount of protein aggregates, followed by a steep increase in the total amount of aggregate. The elapsed time at which these models predict half-conversion of model protein to aggregate varies by less than a factor of two when the intrinsic rate constant for condensation or fibril growth of the protein is varied over many orders of magnitude. It is suggested that this concept can explain why the symptoms of neurodegenerative diseases associated with the aggregation of very different proteins and peptides appear at approximately the same advanced age in humans.